Surfactant-free purification of membrane proteins with intact native membrane environment. (20th May 2011) - Jamshad, Mohammed; Lin, Yu-Pin; Knowles, Timothy J.; Parslow, Rosemary A.; Harris, Craig; Wheatley, Mark; Poyner, David R.; Bill, Roslyn M.; Thomas, Owen R.T.; Overduin, Michael; Dafforn, Tim R.
Abstract : In order to study the structure and function of a protein, it is generally required that the protein in question is purified away from all others. For soluble proteins, this process is greatly aided by the lack of any restriction on the free and independent diffusion of individual protein particles in three dimensions. This is not the case for membrane proteins, as the membrane itself forms a continuum that joins the proteins within the membrane with one another. It is therefore essential that the membrane is disrupted in order to allow separation and hence purification of membrane proteins. In the present review, we examine recent advances in the methods employed to separate membrane proteins before purification. These approaches move away from solubilization methods based on the use of small surfactants, which have been shown to suffer from significant practical problems. Instead, the present review focuses on methods that stem from the field of nanotechnology and use a range of reagents that fragment the membrane into nanometre-scale particles containing the protein complete with the local membrane environment. In particular, we examine a method employing the amphipathic polymer poly(styrene- co -maleic acid), which is able to reversibly encapsulate the membrane protein in a 10 nm disc-like structure ideally suited to purification and further biochemical study.